Effects of different media on the in vivo chondrogenesis of sheep bone marrow stem cells: histological assessment - Alfaqeh, Hamoud Hussein Mohammed; Kienhui, Chua; Bin Saim, Aminuddin; Bint Haji Idus, Ruszymah (2008)
Abstract: Objectives: This study was aimed to examine the effect of two different media on bone marrow stem cells (BMSCs) chondrogenesis in vitro and in vivo.